2017
DOI: 10.1080/10256016.2017.1304936
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variation in the stable isotope composition (δ18O and δ2H) of rain across the tropical island of Sri Lanka

Abstract: Seasonal and spatial variation in δO and δH in rainwater was determined in three selected transects across Sri Lanka, the tropical island in the Indian Ocean. Local meteoric water lines (LMWLs) for three distinguished climatic zones; wet, dry and intermediate were constructed. LMWLs show slight variations in their gradients and respective d-excess values, depending on the air moisture origin, circulation and environmental conditions of each climatic zone. The elevation effect and amount effect could be identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 55 publications
1
24
0
Order By: Relevance
“…1(a)] (Dissanayake & Weerasooriya 1985). The central highlands, reaching 2,524 m above sea level at Pidurutalagala's peak, consist of a number of ridges, peaks, plateaus, basins, valleys, and escarpments (Edirisinghe et al 2017a).…”
Section: Study Site 1 Climate and Physical Settingmentioning
confidence: 99%
See 3 more Smart Citations
“…1(a)] (Dissanayake & Weerasooriya 1985). The central highlands, reaching 2,524 m above sea level at Pidurutalagala's peak, consist of a number of ridges, peaks, plateaus, basins, valleys, and escarpments (Edirisinghe et al 2017a).…”
Section: Study Site 1 Climate and Physical Settingmentioning
confidence: 99%
“…Sri Lanka's climate is controlled by the tropical monsoon system and is classified into two monsoon periods and two intermonsoon periods: the Southwest Monsoon (SWM, from May to September), Northeast Monsoon (NEM, from December to February), First Intermonsoon (FIM, from March to April), and Second Intermonsoon (SIM, from October to November). During the SWM, moist southwesterly winds orographically lift as they cross the central highlands, resulting in a considerable rainfall on the windward side of the highlands, whereas little rain falls on the lee side (Edirisinghe et al 2017a). The NEM is dry and stable compared to the SWM, and windward rainfall during January and February is relatively small (Song et al 1999).…”
Section: Study Site 1 Climate and Physical Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, based on the isotopic values of river waters, significant spatial and temporal variations of the Xijiang River were investigated [26]; Kong et al found that the snowmelt water accounted for more than 57% of runoff of the Kumalak River [1], and more than 53% during the wet season [6]. Based on isotopes and geochemical tracers, streams in plateau regions are mainly replenished by snowmelt and groundwater [27][28][29][30][31][32][33][34][35][36][37][38]. There has been relatively little research on the composition and mechanism of water sources on the Qinghai-Tibet Plateau.…”
Section: Introductionmentioning
confidence: 99%